Potential and Realized Impact of Astroglia Ca2 + Dynamics on Circuit Function and Behavior - Lim, Eunice Y.; Ye, Liang; Paukert, Martin (Frontiers in Cellular Neuroscience, 2021)
Astroglia display a wide range of spontaneous and behavioral state-dependent Ca2+ dynamics. During heightened vigilance, noradrenergic signaling leads to quasi-synchronous Ca2+ elevations encompassing soma and processes across the brain-wide astroglia network. Distinct from this vigilance-associated global Ca2+ rise are apparently spontaneous fluctuations within spatially restricted microdomains. Over the years, several strategies have been pursued to shed light on the physiological impact of these signals including deletion of endogenous ion channels or receptors and reduction of intracellular Ca2+ through buffering, extrusion or inhibition of release. Some experiments that revealed the most compelling behavioral alterations employed chemogenetic and optogenetic manipulations to modify astroglia Ca2+ signaling. However, there is considerable contrast between these findings and the comparatively modest effects of inhibiting endogenous sources of Ca2+. In this review, we describe the underlying mechanisms of various forms of astroglia Ca2+ signaling as well as the functional consequence of their inhibition. We then discuss how the effects of exogenous astroglia Ca2+ modification combined with our knowledge of physiological mechanisms of astroglia Ca2+ activation could guide further refinement of behavioral paradigms that will help elucidate the natural Ca2+-dependent function of astroglia.